Obtaining lipases from byproducts of orange juice processing - Okino-Delgado, Clarissa Hamaio [UNESP]; Fleuri, Luciana Francisco [UNESP] (Elsevier B.V., 2014)
The presence of lipases was observed in three byproducts of orange juice processing: peel, core and frit. The enzymes were characterised biochemically over a wide pH range from neutral (6-7) to alkaline (8-9). The optimal temperature for the activity of these byproducts showed wide range at 20 degrees C to 70 degrees C, indicating fairly high thermostability. The activities were monitored on p-NP-butyrate, p-NP-laurate and p-NP-palmitate. For the first time, lipase activity was detected in these residues, reaching 68.5 lipase U/g for the crude extract from fractions called frit. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Lipase; Byproducts; Orange; Core; Frit; Peel